Two new records of isomyia paurogonita fang and fan, 1986 and sumatria latifrons malloch, 1926 (diptera: Calliphoridae) from northern thailand, with revised key to the species of isomyia - Nophawan Bunchu (2018)
During the annual fly survey at Doi Nang Kaew in Doi Saket District, Chiang Mai Province of Thailand in 2011, Isomyia paurogonita Fang & Fan, 1986 (Diptera: Calliphoridae) and Sumatria latifrons Malloch, 1926 (Diptera: Calliphoridae) were collected for the first time in Thailand. They are the rare species of the subfamily Rhiniinae (tribe Cosminini). Prior to this finding, fifteen species of Isomyia and two species of Sumatria were recorded from Thailand. Therefore, 96 blow fly species have been found in this country. These new locality records of both flies are very important for further research on their biology and ecology in Thailand.